Conventional and optional cardiovascular risk factors in predicting outcome in hemodialysis patients - O. A. Bilevich; N. V. Ovsyannikov; E. V. Usacheva; O. M. Kulikova (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To evaluate the frequency and effects on prognosis of conventional and optional cardiovascular risk (CVR) factors in hemodialysis patients.Material and methods. The study included 82 patients receiving hemodialysis. Clinical examination was carried out. We also assesed heart rate variability and pulse wave velocity by photoplethysmography. To identify significant prognostic factors and determine the range of their values, the decision tree method was used.Results. In hemodialysis patients, the prevalence of hypertension and overweight was higher than in the general population — 100% vs 33,8% and 51,2% vs 29,7%, respectively; the smoking prevalence was comparable — 25,6% vs 25,7%; the prevalence of hypercholesterolemia was lower than in the general population — 45,1% vs 57,6%. Optional CVR factors in hemodialysis patients were as follows: level of pulse pressure, duration of hypertension, hemoglobin level, pulse wave velocity, standard deviation normal to normal (SDNN), left ventricular ejection fraction. Based on a combination of significant CVR factors, 5 rules for predicting a favorable or unfavorable outcome in hemodialysis patients were identified.Conclusion. The use of proposed rules allows to develop novel measures and improve current ones aimed at modifying CVR factors and increasing the survival of hemodialysis patients.